"First Stop Dying": Angola's Christian Seminary as Positive Criminology. (March 2017) - Hallett, Michael; Hays, Joshua; Johnson, Byron; Jang, Sung Joon; Duwe, Grant
This article offers an ethnographic account of the "self-projects" of inmate graduates of Louisiana State Penitentiary's (aka "Angola's") unique prison seminary program. Angola's Inmate Minister program deploys seminary graduates in bivocational pastoral service roles throughout America's largest maximum-security prison. Drawing upon the unique history of Angola, inmates establish their own churches and serve in lay-ministry capacities in hospice, cellblock visitation, tier ministry, officiating inmate funerals, and through tithing with "care packages" for indigent prisoners. Four themes of positive criminology prominently emerge from inmate narratives: (a) the importance of respectful treatment of inmates by correctional administrations, (b) the value of building trusting relationships for prosocial modeling and improved self-perception, (c) repairing harm through intervention, and (d) spiritual practice as a blueprint for positive self-identity and social integration among prisoners.